Pupillary dilation response reflects surprising moments in music. - Liao, Hsin-I (J Eye Mov Res, 2018)
There are indications that the pupillary dilation response (PDR) reflects surprising moments in an auditory sequence such as the appearance of a deviant noise against repetitively presented pure tones (4), and salient and loud sounds that are evaluated by human paricipants subjectively (12). In the current study, we further examined whether the reflection of PDR in auditory surprise can be accumulated and revealed in complex and yet structured auditory stimuli, i.e., music, and when the surprise is defined subjectively. Participants listened to 15 excerpts of music while their pupillary responses were recorded. In the surprise-rating session, participants rated how surprising an instance in the excerpt was, i.e., rich in variation versus monotonous, while they listened to it. In the passive-listening session, they listened to the same 15 excerpts again but were not involved in any task. The pupil diameter data obtained from both sessions were time-aligned to the rating data obtained from the surprise-rating session. Results showed that in both sessions, mean pupil diameter was larger at moments rated more surprising than unsurprising. The result suggests that the PDR reflects surprise in music automatically.